The Increase of Osteoporotic Hip Fractures and Associated One-Year Mortality in Poland: 2008–2015 - Glinkowski, Wojciech (J Clin Med, 2019)
Introduction: Hip fractures are a worldwide public health issue associated with significant mortality. Previous Polish studies reported an increasing trend in the number of hip fractures for both men and women, although lower than most other European countries. Materials and Methods: The Polish National Database was analyzed to examine osteoporotic hip fractures in the population aged 50 and over. Hip fracture incidence, rate, one-year mortality, and postoperative length of hospitalization were analyzed using the national health system data. Hospital discharge registry ICD-10 codes were reviewed from 2008 to 2015. Results: The incidence of hip fractures increased in both women and men by 19.4% and 14.2%, respectively. The female to male fracture ratio was 2.46. Mean postoperative hospitalization decreased from 13.6 to 11.2 days. The one-year mortality ranged between 30.45% to 32.8% for men and 26.2% to 28% for women. Of note, women aged 80–89 had the highest one-year mortality, 50.7%–55.4% after femoral neck fracture and 53%–58.5% after a pertrochanteric fracture. Conclusions: Hip fractures in Poland are increasingly more prevalent in the aging population. The unfavorable trends observed in this study indicate higher annual mortality after hip fracture, compared with other European countries.